Assessment of selected physical, chemical, and sensory characteristics of muscovado produced in Antique. - Payofelin, Frances Joan Chavez (2017.)
Muscovado is a type of non-centrifugal cane sugar that takes its characteristics flavor and taste from molasses. The Visayas region is the largest producer of muscovado with the province of Antique having the most number of mills. There is a demand for Antique muscovado in local industries but the variable quality of the product is yet to be solved. This study aimed to determine factors that result to the variability of the quality of muscovado produced in Laua-an, Patnongon and Belison, Antique. They were assessed in terms of pH, total soluble solids (TSS), moisture content, ash content, filth or extraneous matter, and color. The assessed muscovado samples had a mean pH range of 4.41 to 5.70, mean TSS range of 48.430Brix to 54.910Brix, mean moisture content range of 2.72% to 4.41% mean ash content range of 1.14% to 2.28%, and mean filth of 0.61% to 0.92%. One way ANOVA at 95% level of confidence showed significant differences in pH, TSS, moisture content, and ash content of muscovado. The color ranged from golden brown to dark brown. In terms of moisture content, ash content, and color, all muscovado from five processors passed Sugar Regulatory Administration?s (SRA) proposed standards. The most preferred muscovado (MPM) was determined based on color. The MPM was from Processor B. It was analyzed for reducing sugar, antioxidant activity, and sensory evaluation in terms of taste and aroma. Reducing sugar was found to be 8.78%. The taste and aroma of MPM was found to be both moderatey strong. Pearson correlation determined that there is a positive linear relationship between color and pH, and color and moisture content with correlation coefficients of 0.998 and 0.934, respectively, while there is a negative linear relationship between color and antioxidant activity with a correlation coefficient of -0.066.
Thesis - B.S. (Food Technology) - School of Technology, University of the Philippines Visayas.
Keywords: Muscovado; Cane sugar; Sugar; Molasses